Solution of discrete oscillating system on personal computer - Phong, Dinh Van (Vietnam Journal of Mechanics, 1993)
The article is devoted an algorithm for deriving mass matrix, stiffness matrix and damping matrix for oscillating discrete system. The algorithm is common setting equation of motion. This technique enables solving different problems of oscillating system, especially a problem of parameters optimization, by numerical methods. Comparison of different methods realized on personal computers was done.